200 years of sovereign debt crises: Serial restructurings may be accompanied by higher creditor losses - Josefin Meyer (DIW Weekly Report, 2024)
Many sovereign defaults have occurred worldwide over the past 200 years. An analysis of 321 sovereign debt restructurings since 1815 shows that foreign private and institutional investor losses were 43 percent on average. Notably, beginning in the 1970s, several debt exchanges have increasingly been required to resolve a default. To understand this new phenomenon better, this Weekly Report looks at total creditor losses across all restructurings during a default spell. Instead of focusing on each individual restructuring, the cumulative haircut adds up all losses across a default spell. These calculations show that debt crises with serial restructurings resulted in greater overall losses for creditors than a major one-off restructuring. The results conclude that it makes sense to perform a debt sustainability analysis independently and in a timely manner when determining the size of a haircut. This could lessen debt restructurings with shallow haircuts that do not manage to bring countries back to their sustainable debt path.
Keywords: E4; F3; G1; N0; 330; Sovereign debt; Sovereign debt crises and defaults; haircuts